Making the Most of the African Continental Free Trade Area : Leveraging Trade and Foreign Direct Investment to Boost Growth and Reduce Poverty - Echandi, Roberto; Maliszewska, Maryla; Steenbergen, Victor (Washington, DC: World Bank, 2022)
The creation of the African Continental Free Trade Area (AfCFTA) provides a unique opportunity to boost growth, cut poverty, and reduce Africa’s dependence on the boom and-bust commodity cycle. A World Bank (2020) report estimates that the AfCFTA has the potential to raise income in the continent by 7 percent by 2035 and lift 40 million people out of extreme poverty, mainly by spurring intraregional trade (termed the “AfCFTA trade scenario” for purposes of this analysis). Reductions in nontariff barriers on goods and services and improvements in trade facilitation measures will account for about two thirds of the US$450 billion in potential income gains by removing long delays across most of the continent’s borders and lowering compliance costs in trade, making it easier for African businesses to become integrated into regional and global supply chains. This report builds on that earlier study by including potential gains arising from greater flows of foreign direct investment (FDI), termed the “AfCFTA FDI broadscenario,” and from deeper integration beyond trade, the “AfCFTA FDI deep scenario.” FDI has traditionally been low in Africa. The AfCFTA is likely to attract cross-border investment by eliminating tariff and nontariff barriers and replacing the existing patchwork of bilateral and regional trade deals with a single, unified market. Investors in any one of 55 member countries will have access to a continent of 1.3 billion people with a combined GDP of US$3.4 trillion. Integration in global and regional value chains offers a further magnet for FDI and the jobs, investment, and know-how that FDI brings.